Design of a new backstepping controller for control of microgrid sources inverter - Mahmoud Zadehbagheri; Mohammad Javad Kiani; Tole Sutikno; Rasoul Arvin Moghadam (Institute of Advanced Engineering and Science, 2022)
Emergency power supply is becoming an important capability for many home or industrial electronic and computer devices. Therefore, the performance of the designed uninterruptible power supplies (UPS) inverters has low distortion at the output voltage. Initially, such inverters were controlled by proportional integral (PI) control classic rules. This method is difficult to understand the limitations of stability and to apply transient response to strong external disturbances. In this paper, an inverter is simulated and offered for single-phase and three-phase voltage controlled by a non-linear controller. For this purpose, a comparison has been made between the controller performance and the PI controller. In the first step, there is a backstepping regulator that uses the stability tool next to the Lyapunov function. And the other regulator operates according to the PI method. The performance of these two regulators is simulated during a change in reference or a load change in MATLAB. Also, a method of feedback voltage control based on the Lyapunov theory for controlling of the distributed generation (DG) unit independent Inverter is presented. The proposed controller is not only simple, but also against the sudden changes in load and the unspecified system is resistant.